Vitamin d deficiency with high parathyroid hormone levels is related to late onset SEPSIS among preterm infants - I. Tofe-Valera; J. L. Pérez-Navero; J. Caballero-Villarraso; M. D. Cañete; R. Villa-Jiménez; M. J. De la Torre-Aguilar (BMC, 2023)
Abstract Summary Preterm infants (PTs) are at greater risk for vitamin D deficiency, which relates to the possibility of a higher incidence of comorbidities. Our goal was twofold, 1) to monitor vitamin D, calcium, phosphorus, parathyroid hormone (PTH), matrix metalloproteinase-8 (MMP-8) serum levels at three-time points during hospitalization, and 2) to assess the association between 25-hydroxyvitamin D (25OHD) levels and outcomes in PTs. Methods We carried out a follow-up on 50 Caucasian PTs ≤ 32 weeks of gestational age (GA) and/or ≤ 1500 g birth weight at 28 days and at 4 months. PTs were divided into two subgroups for tests of association with clinical outcomes based on vitamin D deficient infants 25(OH) D cord blood levels: ≤ 20 ng/ml). At an initial stage, 25(OH) D levels were determined in maternal/preterm blood samples and were compared to full term delivery infants. Results There were no differences in 25(OH) D serum levels at birth when comparing PTs to term infants, or regarding maternal levels. A strong positive correlation was detected between maternal and neonatal 25(OH) D serum levels among PTs and term infants (r: 0.466; p < 0.001). Neonates with vitamin D deficiency did not present a higher incidence of comorbidities. PTs were classified in two subgroups based on vitamin D and PTH (group 1: vitamin D < 20 ng/mL and PTH > 60 pg/mL; group 2: vitamin D > 20 and PTH < 60 pg/mL). The PTs in group 1 showed a higher incidence of LOS (RR: 2; 95% CI: 1.31-3.55). No relationship was observed between MMP-8 serum levels and the incidence of sepsis. Conclusions This study did not find any evidence of an increase in preterm birth risk related to vitamin D level at birth. Vitamin D deficiency by itself is not associated with a higher incidence of comorbidities. However, the binomial vitamin D-PTH must be taken into consideration.